Efficacy and Safety of Oral Midazolam Sedation Compared with its Combination with Hydroxyzine Use in Pediatric Dentistry: A Systematic Review - Gustavo Henrique Porto Oliveira; Diogo Gomes Brandão; Fernando José Camello de Lima; Patricia Batista Lopes do Nascimento; Priscylla Gonçalves Correia Leite de Marcelos; Daniela Maria Carvalho Pugliesi; Leopoldo Cosme-Silva; Valdeci Elias dos Santos Júnior (Association of Support to Oral Health Research (APESB), 2023)
Objective: To assess the efficacy and safety of the use of midazolam as monotherapy, compared to the associated use of midazolam and hydroxyzine for minimum and moderate sedation of children in dental offices, using data obtained from clinical trials. Material and Methods: A systematic review protocol was developed and registered on PROSPERO (CR42020208633). An electronic search was carried out in Pubmed, Lilacs, Science Direct, Open Gray, Web of Science, and central Cochrane Library. No language restrictions were included. Clinical trials were carried out with children aged 0-12 years, using midazolam as monotherapy compared to the use of midazolam associated with hydroxyzine to verify the effectiveness and safety of oral sedation. The quality of the studies was individually assessed and grouped using the RoB 2 (Revised Cochrane risk-of-bias tool for randomized trials) and GRADE (Grading of Recommendations Assessment, Development and Evaluation) systems, respectively. Results: A total of 749 studies were found. After analyzing the inclusion and removal of duplicates, two studies were analyzed for the quality of evidence. Through this analysis, it was possible to verify the very low level of scientific evidence on the superiority of the efficacy and safety of the combined use of midazolam and hydroxyzine for oral sedation in children in dental offices. Conclusion: The conflicting results and limitations of the studies enabled to establish that there is insufficient evidence to support the use of these drugs combined. There is only evidence for the use of midazolam as monotherapy.